MEMAKNAI TERMINOLOGI FAKIR DAN MISKIN DALAM KONTEK AMIL ZAKAT MASA KINI - Ritonga, A. Rahman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Other than having the religious dimension hablum minallah, zakat also reflects social dimension hablum minannas. These two dimensions will be realized only if the implementation is in line with Islamic law which is based on the Qur’an and the sunnah of the prophet. The most dominant receiver of zakat knows as mustahik zakat is the needy and the poor. The distribution of the zakat can be carried out by national committee of zakat formed by the government based on the constitution and can also be carried out directly by the one who intended to pay zakat known as muzakki to the needy and the poor known as mustahik. Lately, the distribution of zakat has caused some humanity problems; it even has become the most addressed social issues among the muslim community since there is an indication that the applications violate islamic laws. Therefore, this book tries to address the problematic issues in the distribution of zakat in order to prevent the distribution problem so that zakat can be regarded as a social religious activity which can also be highly valued by Allah.